Vegetation indices simulated from different sensors for the estimation of biophysical variables of common bean - Monteiro, Priscylla Ferraz Câmara; Angulo Filho, Rubens; Xavier, Alexandre Cândido; Monteiro, Rodrigo Otávio Câmara (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the vegetation indices and red and infrared bands of the HRVIR, ETM+ and Modis sensors, in the estimations of leaf area index and grain yield of common bean. The experiment was carried out in a randomized block design, with split plots and four irrigation levels (179.5, 256.5, 357.5, and 406.2 mm), three N rates (0.0, 80.0 and 160.0 kg ha-1), and four replicates. The reflectance measurements were obtained through the Spectron SE‑590, at R6 stage, on 48 plots. Simple ratio, normalized difference vegetation index, soil‑adjusted vegetation index, and enhanced vegetation index were tested. The vegetation indices were efficient to estimate the leaf area index (LAI) and grain yield. The vegetation indices and infrared band show the same potential to estimate LAI, when considering the spectral resolution of Modis, ETM+ and HRVIR.